Exploring Health Care Providers' Views About Initiating End-of-Life Care Communication. (May 2017) - Nedjat-Haiem, Frances R.; Carrion, Iraida V.; Gonzalez, Krystana; Ell, Kathleen; Thompson, Beti; Mishra, Shiraz I.
Numerous factors impede effective and timely end-of-life (EOL) care communication. These factors include delays in communication until patients are seriously ill and/or close to death. Gaps in patient–provider communication negatively affect advance care planning and limit referrals to palliative and hospice care. Confusion about the roles of various health care providers also limits communication, especially when providers do not coordinate care with other health care providers in various disciplines. Although providers receive education regarding EOL communication and care coordination, little is known about the roles of all health care providers, including nonphysician support staff working with physicians to discuss the possibility of dying and help patients prepare for death. This study explores the perspectives of physicians, nurses, social workers, and chaplains on engaging seriously ill patients and families in EOL care communication. Qualitative data were from 79 (medical and nonmedical) providers practicing at 2 medical centers in Central Los Angeles. Three themes that describe providers' perceptions of their roles and responsibility in talking with seriously ill patients emerged: (1) providers' roles for engaging in EOL discussions, (2) responsibility of physicians for initiating and leading discussions, and (3) need for team co-management patient care. Providers highlighted the importance of beginning discussions early by having physicians lead them, specifically due to their medical training and need to clarify medical information regarding patients' prognosis. Although physicians are a vital part of leading EOL communication, and are at the center of communication of medical information, an interdisciplinary approach that involves nurses, social workers, and chaplains could significantly improve patient care.